Plasma appearance and correlation between coffee and green tea metabolites in human subjects - Renouf, Mathieu; Guy, Philippe; Marmet, Cynthia; Longet, Karin; Fraering, Anne-Lise; Moulin, Julie; Barron, Denis; Dionisi, Fabiola; Cavin, Christophe; Steiling, Heike; Williamson, Gary (British journal of nutrition, 2010)
Coffee and green tea are two of the most widely consumed hot beverages in the world. Their respective bioavailability has been studied separately, but absorption of their respective bioactive phenolics has not been compared. In a randomised cross-over design, nine healthy subjects drank instant coffee and green tea. Blood samples were collected over 12 h and at 24 h to assess return to baseline. After green tea consumption, ( − )-epigallocatechin (EGC) was the major catechin, appearing rapidly in the plasma; ( − )-EGC gallate (EGCg) and ( − )-epicatechin (EC) were also present, but ( − )-EC gallate and C were not detected. Dihydroferulic acid and dihydrocaffeic acid were the major metabolites that appeared after coffee consumption with a long time needed to reach maximum plasma concentration, suggesting metabolism and absorption in the colon. Other phenolic acid equivalents (caffeic acid (CA), ferulic acid (FA) and isoferulic acid (iFA)) were detected earlier, and they peaked at lower concentrations. Summations of the plasma area under the curves (AUC) for the measured metabolites showed 1·7-fold more coffee-derived phenolic acids than green tea-derived catechins (P = 0·0014). Furthermore, we found a significant correlation between coffee metabolites based on AUC. Inter-individual differences were observed, but individuals with a high level of CA also showed a correspondingly high level of FA. However, no such correlation was observed between the tea catechins and coffee phenolic acids. Correlation between AUC and maximum plasma concentration was also significant for CA, FA and iFA and for EGCg. This implies that the mechanisms of absorption for these two classes of compounds are different, and that a high absorber of phenolic acids is not necessarily a high absorber of catechins.